2021
DOI: 10.1158/0008-5472.can-21-0752
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Radiation-Induced Senescence in the Brain Tumor Microenvironment Attenuates Glioblastoma Recurrence

Abstract: Glioblastomas (GBM) are routinely treated with ionizing radiation (IR) but inevitably recur and develop therapy resistance. During treatment, the tissue surrounding tumors is also irradiated. IR potently induces senescence, and senescent stromal cells can promote the growth of neighboring tumor cells by secreting factors that create a senescence-associated secretory phenotype (SASP). Here, we carried out transcriptomic and tumorigenicity analyses in irradiated mouse brains to elucidate how radiotherapy-induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 65 publications
3
68
0
Order By: Relevance
“…This simple view has recently shifted towards recognizing the central importance of the TME 15 and a growing body of literature are now investigating the impacts of RT on TME and tumor resistance. At least, three recent publications reported that an irradiated TME increases GBM aggressiveness in orthotopic murine models 6,16,17 with no or limited investigation of underlying mechanisms. In the present work, using relevant in vitro and in vivo models, we demonstrate that alteration of the vascular TME by RT directly impacts relapsing tumor aggressiveness upon radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple view has recently shifted towards recognizing the central importance of the TME 15 and a growing body of literature are now investigating the impacts of RT on TME and tumor resistance. At least, three recent publications reported that an irradiated TME increases GBM aggressiveness in orthotopic murine models 6,16,17 with no or limited investigation of underlying mechanisms. In the present work, using relevant in vitro and in vivo models, we demonstrate that alteration of the vascular TME by RT directly impacts relapsing tumor aggressiveness upon radiation.…”
Section: Discussionmentioning
confidence: 99%
“…By conferring diverse fitness advantages to tumor cells, genomic remodeling gives rise to multiple and heterogeneous subpopulations of RT-surviving GBM cells and contributes to intratumoral heterogeneity, which has been described as the root cause of tumor relapse aggressiveness and resistance to treatments. A recent study proposed a different hypothesis where pre-irradiation of the brain accelerates GBM relapse in orthotopic mouse models, in particular through radio-induced astrocyte senescence 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This was best demonstrated in acute myeloid leukemia models where relapse is mediated by a senescence-like resilience phenotype induced by exposure to therapy ( Duy et al, 2021 ). In addition to the precipitation of senescence in tumor cells, exposure to therapy also induces senescence in the tumor microenvironment which has also been implicated in cancer relapse ( Fletcher-Sananikone et al, 2021 ). In this case, relapse is propagated through the non-cell-autonomous effect of senescence mediated through the senescence-associated secretory phenotype ( Demaria et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high lethality of GBM is largely caused by its infiltrative invasion and recurrence at adjacent or distant regions of the brain after surgery [8,9]. The metastasis of cancer cells commences with the invasion of adjacent cells and the formation of new tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%